Interaction of Aβ1−42 chains and fibrillary seeds studied by all‐atom molecular dynamics simulations. Issue 6 (16th December 2020) - Dorosh, Lyudmyla; Wu, Min; Stepanova, Maria
Abstract: We apply all‐atom molecular dynamics simulations to investigate interactions of amyloid beta (A β ) fibril seeds with natively disordered A β chains, a process associated with the onset of Alzheimer's disease. The simulations captured attachment of A β chains to the fibrils suggesting an onset of both fibril's elongation and secondary nucleation, with a stronger affinity of attachment leading to elongation. Choice of fibril's model appears important for the propensity to recruit A β chains from solution and retain them adsorbed. Nuclear magnetic resonance‐based and cryo‐electron microscopy derived models of A β fibrils exhibited significant differences in the interaction with individual A β chains, as well as in structural and dynamical stability in solution.